Individual Factors Influencing Utilization of Research4Life Databases by National Agricultural Research Institute Scientists in Nigeria. Issue 1 (2nd January 2017) - Obasuyi, Luke Osamudiamen; Okwilagwe, Oshiotse Andrew
ABSTRACT: This study is part of a doctoral thesis investigating individual factors influencing utilization of Research4Life databases by NARI scientists in Nigeria. The study adopted descriptive research design of the correlational type. From a population of 1, 205, 744 scientists were selected using simple random and stratified random sampling techniques. The questionnaire used for data collection consisted of 105 questions arranged in five sections. Percentage, mean, correlation, and multiple regression were used to analyze the data. Results indicate that six individual factors influenced utilization of Research4Life databases. Computer anxiety and computer and Internet self-efficacy made significant contributions to utilization of Research4Life databases.